Kesesuaian Lahan Tanaman Ubi Jalar (Ipomoea batatas) dan Ubi Kayu (Manihot esculenta) di Daerah Pesisir Pantai Utara Manokwari - Inggerarda Redjauw; Rudolf K. Tukayo; Aplena Elen Siane Bless (Agrotek, 2022)
Land suitability is the ability of a land for certain uses. The purpose of this study was to study soil salinity and potential land suitability for cultivation of food crops (cassava and sweet potato) from two different locations in Yoom II Village, North Manokwari District. The research method used was the observation method with survey techniques. Parameters observed were soil physical properties (texture, structure, soil color, surface rock, effective depth, water content) and soil chemical properties (soil pH and soil salinity). The results of the evaluation of land suitability for cassava plants at the two research locations, namely close to the coast (DP) and far from the coast (JP) generally had an actual land suitability class of S3 or marginally appropriate. The main limiting factors for the growth of cassava and sweet potato are surface rock and soil depth, as well as soil pH. Meanwhile, soil salinity was not a limiting factor because the electrical conductivity of the soil is less than 2 dSm-1. Improvement efforts that can be made to increase the land suitability class to be quite suitable (S2) are by cleaning the surface rock and adding organic matter to reduce soil pH.